Effect of the gene silencing of phosphorus transporters on phosphorus absorption across primary cultured duodenal epithelial cell monolayers of chick embryos - Ting-ting LI; Na LU; Yu-xin SHAO; Li-yang ZHANG; Lin LU; Zong-ping LIU; Xu-gang LUO; Xiu-dong LIAO (Journal of Integrative Agriculture)
The aim of the study was to investigate whether phosphorus (P) transporters, type IIb sodium-dependent phosphate cotransporter (NaP-IIb) and inorganic phosphate transporter 2 (PiT2), were directly involved in P absorption across primary cultured duodenal epithelial cell monolayers of chick embryos. The siRNAs against NaP-IIb or PiT2 were designed, synthesized and transfected into primary cultured duodenal epithelial cells of chick embryos. Then, the inhibitory efficiency of siRNAs against NaP-IIb or PiT2 was analyzed, and the most efficacious siRNAs were selected to be used for subsequent P absorption experiments. Briefly, primary cultured duodenal epithelial cells of chick embryos were transfected with either NaP-IIb or PiT2 siRNAs and grown in confluent monolayers on transwell plates. The untransfected or transfected cell monolayers were then incubated in an uptake medium containing 0 or 0.25 mmol L–1 of P as KH2PO4 to measure the P absorption across duodenal epithelial cell monolayers. The results showed that among the siRNAs designed, si-1372 and si-890 were demonstrated to be the most effective in inhibiting the NaP-IIb and PiT2 expressions, respectively. Supplemental P increased (P=0.065) the protein abundance of PiT2 and enhanced (P<0.0001) P absorption in primary cultured duodenal epithelial cell of chick embryos. Furthermore, NaP-IIb silencing decreased (P=0.07) P absorption across duodenal epithelial cell monolayers, while PiT2 silencing had no effect (P=0.345). It is concluded that the NaP-IIb, but not PiT2, might be directly involved in the P absorption of chick duodenal epithelial cells.